A high Young's modulus solid electrolyte, all-solid-state lithium battery and preparation method

By using high Young's modulus solid electrolyte in solid-state lithium batteries, the preparation process is simplified through melting and rapid cooling processes, the solid contact problem in solid-state lithium batteries is solved, the mechanical stability and cycling performance of the battery are improved, and the battery life is extended .

CN118993141BActive Publication Date: 2025-01-10CRINM (GUANGDONG) INST FOR ADVANCED MATERIALS & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411460569.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-10
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

The contact problem between solid and solid in solids in solid lithium batteries leads to low lithium ion transmission efficiency, interfacial chemical reactions and mechanical stress problems, affecting the electrochemical performance and safety of the battery. The preparation process of existing methods to improve the mechanical properties of solid electrolytes is complicated. Difficult to control.

Method used

By melting the electrolyte raw material under dry and anaerobic conditions and rapidly cooling the cooling rate is controlled to 600-1200℃/min, grinding it into powder, high-yang's modulus solid electrolyte is prepared, and Gaoyang is set in all-solid lithium batteries modulus solid electrolyte to improve interface stability.

Benefits of technology

The high Young's modulus of the electrolyte is achieved, the circulation performance and efficiency of lithium batteries are improved, the service life of the battery is extended, and the preparation process is simplified.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118993141B_ABST
    Figure CN118993141B_ABST
Patent Text Reader

Abstract

The invention discloses a high Young's modulus solid electrolyte, an all-solid-state lithium battery and a preparation method, belonging to the field of battery technology. The preparation method of the high Young's modulus solid electrolyte is to first melt the electrolyte raw material under dry oxygen-free conditions, then rapidly cool it into a solid block, and then grind it into powder. The process is simple, and the prepared solid electrolyte has good mechanical properties. The all-solid-state lithium battery made using the solid electrolyte can greatly improve the interface stability of the lithium battery, improve the solid-solid mechanical contact, and improve the cycle performance and efficiency of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and in particular relates to a high Young's modulus solid electrolyte, an all-solid-state lithium battery and a preparation method thereof. Background Art

[0002] Solid-state lithium-ion batteries have become a current research hotspot and future research trend due to their advantages such as high safety, high energy density and cycle performance. At the same time, people have also noticed that compared with liquid lithium-ion batteries, there are problems with solid-solid contact in solid-state batteries, which will lead to low efficiency of lithium ion transmission, chemical reactions at the interface, and mechanical stress problems. The stability of the solid-solid interface will seriously affect the electrochemical performance and safety of the battery, which also hinders the practical application of solid-state batteries.

[0003] At present, most of the research on the interface problems of solid-state batteries focuses on chemical reactions. However, unfavorable electrochemical-mechanical dynamics may lead to poor material utilization, mechanical degradation and poor ion transport, affecting the performance and life of the battery. Mechanical properties are important physical properties of solid materials, and the mechanical behavior they exhibit has an important influence on the mechanical stability and electrochemical performance of solid-state batteries. Therefore, it is of great significance to study the mechanical properties of the materials of each component of solid-state batteries and the mechanical failure behavior caused by them. The solid electrolyte is in direct contact with the positive and negative electrodes, and its mechanical properties have an important influence on the mechanical integrity of the positive and negative electrodes. The mechanical stability of solid-state lithium batteries depends largely on the mechanical properties of the solid electrolyte. Therefore, how to develop an electrolyte that can improve the physical and mechanical stability of solid-state batteries and release the structural stress accumulated during the cycle is a technical problem that technicians in this field need to solve urgently. At present, most strategies to improve the mechanical properties of solid electrolytes include regulating their own phase composition, grain size, porosity, etc., or reducing the defects of the electrolyte and improving its performance by doping and adding other components to the electrolyte. However, the preparation process of these regulation methods is relatively complicated and it is difficult to control variables. Summary of the invention

[0004] The purpose of the embodiment of the present invention is to provide a method for preparing a high Young's modulus solid electrolyte, which has a simple process and has good mechanical properties.

[0005] Another object of an embodiment of the present invention is to provide a method for preparing an all-solid-state lithium battery, which has a simple process and the prepared all-solid-state lithium battery has good electrochemical performance and a long service life.

[0006] The embodiment of the present invention is achieved as follows:

[0007] An embodiment of the present invention provides a method for preparing a high Young's modulus solid electrolyte, comprising the following steps:

[0008] S1: Melting the electrolyte raw materials under dry oxygen-free conditions, with a melting temperature of 405-700°C and a melting time of 1-20h;

[0009] S2: Rapidly cool the molten liquid electrolyte into a solid block, and the cooling rate is controlled at 600-1200℃ / min;

[0010] S3: Grinding the cooled solid block into powder to prepare a high Young's modulus solid electrolyte.

[0011] Furthermore, in step S1, the melting temperature is 405°C and the time is 20 hours, or the melting temperature is 500°C and the time is 15 hours, or the melting temperature is 600°C and the time is 10 hours, or the melting temperature is 700°C and the time is 1 hour.

[0012] Furthermore, in step S2, the cooling rate is 600°C / min, 800°C / min, 1000°C / min or 1200°C / min.

[0013] Furthermore, the electrolyte raw material is Li 2+x M x N 1-x Cl6, wherein M is one or more of Y, Er, Yb, Ho, In, La, Sc, Tb, Dy; N is one or two of Zr and Hf; 0≤x≤1.

[0014] Furthermore, the electrolyte raw material is Li 2.5 Y 0.5 Zr 0.5 Cl6、Li 2.6 Y 0.6 Hf 0.4 Cl6, Li3YCl6 or Li 2.5 Yb 0.5 Hf 0.5 Cl6.

[0015] An embodiment of the present invention further provides a high Young's modulus solid electrolyte, which is obtained by the above-mentioned method for preparing the solid electrolyte.

[0016] An embodiment of the present invention also provides an all-solid-state lithium battery, comprising a positive electrode active material layer, a negative electrode active material layer and the high Young's modulus solid electrolyte described above, wherein the high Young's modulus solid electrolyte is pressed into a block and arranged between the positive electrode active material layer and the negative electrode active material layer.

[0017] An embodiment of the present invention further provides a method for preparing the above-mentioned all-solid-state lithium battery, comprising the following steps:

[0018] A1: The layered cathode material and the high Young's modulus solid electrolyte are mixed in a mass ratio of 7:3, and then ground into powder to obtain a cathode powder;

[0019] A2: Weigh an appropriate amount of sulfide solid electrolyte and put it into the mold battery liner, apply a pressure of 100 MPa to press it to obtain the first electrolyte layer, then take an appropriate amount of high Young's modulus solid electrolyte and evenly place it on one side of the thickness direction of the first electrolyte layer, and apply a pressure of 150 MPa to press it to obtain the second electrolyte layer;

[0020] A3: The positive electrode powder is evenly placed on the side of the second electrolyte layer away from the first electrolyte layer, and a pressure of 350 MPa is applied to press the positive electrode powder to obtain a positive electrode active material layer;

[0021] A4: Place a metal indium sheet on the side of the first electrolyte layer away from the second electrolyte layer, and apply a pressure of 50 MPa to press the sheet to obtain a negative electrode active material layer;

[0022] A5: Place the inner liner into the mold battery, lock and seal it to make an all-solid-state lithium battery.

[0023] The beneficial effects of the present invention are:

[0024] (1) The electrolyte preparation method provided in the embodiment of the present invention has a simple process, and the solid electrolyte prepared by rapid cooling has a higher Young's modulus and better mechanical properties.

[0025] (2) The all-solid-state lithium battery provided by the embodiment of the present invention can greatly enhance the interface stability of the lithium battery, improve the solid-solid mechanical contact, and improve the cycle performance and efficiency of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 The CT three-dimensional pore image of the cathode composite material after the battery made of the solid electrolyte of Example 1 was cycled 100 times;

[0028] Figure 2 The CT three-dimensional pore image of the cathode composite material after the battery made of the solid electrolyte of Comparative Example 1 was cycled 100 times;

[0029] Figure 3 is a focused ion beam scanning electron microscope image of Example 1;

[0030] Figure 4 This is the focused ion beam scanning electron microscope image of comparative example 1. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.

[0032] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention as claimed but is merely representative of selected embodiments of the present invention.

[0033] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features of the embodiments may be combined with each other.

[0034] The present invention provides a method for preparing a high Young's modulus solid electrolyte, comprising the following steps:

[0035] S1: Melting the electrolyte raw materials under dry oxygen-free conditions, with a melting temperature of 405-700°C and a melting time of 1-20h;

[0036] S2: Rapidly cool the molten liquid electrolyte into a solid block, and the cooling rate is controlled at 600-1200℃ / min;

[0037] S3: Grinding the cooled solid block into powder to prepare a high Young's modulus solid electrolyte.

[0038] In the present invention, the electrolyte raw material is Li 2+x M x N 1-x Cl6, where M is one or more of Y, Er, Yb, Ho, In, La, Sc, Tb, Dy; N is one or two of Zr and Hf; 0≤x≤1. For example, Li 2.5 Y 0.5 Zr 0.5 Cl6、Li 2.6 Y 0.6 Hf 0.4 Cl6, Li3YCl6 or Li 2.5 Yb 0.5 Hf 0.5 Cl6 etc.

[0039] Example 1

[0040] In Example 1 of the present invention, a high Young's modulus solid electrolyte is prepared by the following method:

[0041] S1: Li 2.5 Y 0.5 Zr 0.5 Cl6 melts under dry oxygen-free conditions at a melting temperature of 405°C and a melting time of 20h;

[0042] S2: Rapidly cool the molten liquid electrolyte into a solid block, and the cooling rate is controlled at 600℃ / min;

[0043] S3: Grinding the cooled solid block into powder to prepare a high Young's modulus solid electrolyte.

[0044] Example 2

[0045] Example 2 of the present invention adopts the following method to prepare a high Young's modulus solid electrolyte:

[0046] S1: Li 2.5 Y 0.5 Zr 0.5 Cl6 melts under dry oxygen-free conditions at a melting temperature of 600°C and a melting time of 10 hours;

[0047] S2: Rapidly cool the molten liquid electrolyte into a solid block, and the cooling rate is controlled at 1000℃ / min;

[0048] S3: Grinding the cooled solid block into powder to prepare a high Young's modulus solid electrolyte.

[0049] Example 3

[0050] Example 3 of the present invention adopts the following method to prepare a high Young's modulus solid electrolyte:

[0051] S1: Li 2.6 Y 0.6 Hf 0.4 Cl6 melts under dry oxygen-free conditions at a melting temperature of 500°C and a melting time of 15h;

[0052] S2: Rapidly cool the molten liquid electrolyte into a solid block, and the cooling rate is controlled at 800℃ / min;

[0053] S3: Grinding the cooled solid block into powder to prepare a high Young's modulus solid electrolyte.

[0054] Example 4

[0055] Example 4 of the present invention adopts the following method to prepare a high Young's modulus solid electrolyte:

[0056] S1: Li3YCl6 is melted under dry oxygen-free conditions at a melting temperature of 700°C for 1 h;

[0057] S2: Rapidly cool the molten liquid electrolyte into a solid block, and the cooling rate is controlled at 1200℃ / min;

[0058] S3: Grinding the cooled solid block into powder to prepare a high Young's modulus solid electrolyte.

[0059] Example 5

[0060] Example 5 of the present invention adopts the following method to prepare a high Young's modulus solid electrolyte:

[0061] S1: Li 2.5 Yb 0.5 Hf 0.5 Cl6 melts under dry oxygen-free conditions at a melting temperature of 550°C and a melting time of 8 hours;

[0062] S2: Rapidly cool the molten liquid electrolyte into a solid block, and the cooling rate is controlled at 900℃ / min;

[0063] S3: Grinding the cooled solid block into powder to prepare a high Young's modulus solid electrolyte.

[0064] Comparative Example 1

[0065] Comparative Example 1 The solid electrolyte was prepared by the following method:

[0066] S1: Li 2.5 Y 0.5 Zr 0.5 Cl6 melts under dry oxygen-free conditions at a melting temperature of 405°C and a melting time of 20h;

[0067] S2: naturally cool the molten liquid electrolyte into a solid block;

[0068] S3: Grinding the cooled solid block into powder to prepare a solid electrolyte.

[0069] Comparative Example 2

[0070] Comparative Example 2 The solid electrolyte was prepared by the following method:

[0071] S1: Li 2.5 Yb 0.5 Hf 0.5 Cl6 melts under dry oxygen-free conditions at a melting temperature of 550°C and a melting time of 8 hours;

[0072] S2: naturally cool the molten liquid electrolyte into a solid block;

[0073] S3: Grinding the cooled solid block into powder to prepare a solid electrolyte.

[0074] The solid electrolytes of Examples 1 to 5, Comparative Examples 1 and 2 were tested for Young's modulus in sequence. The testing method was as follows: 150 mg of the solid electrolyte was placed in a mold battery in a glove box and pressed into a sheet at a pressure of 400 MPa. The sheet sample was then taken out and the mechanical curve was measured using an atomic force microscope. The Young's modulus was analyzed based on the mechanical curve.

[0075] The test results are shown in Table 1:

[0076] Table 1

[0077] serial number Young's modulus (GPa) Example 1 13 Example 2 16 Example 3 9 Example 4 12 Example 5 15 Comparative Example 1 5 Comparative Example 2 3

[0078] It can be seen from Table 1 that the solid electrolyte made by rapid cooling has a higher Young's modulus, is more difficult to deform under the same stress, maintains good contact with the material when the positive electrode material undergoes volume expansion, and has better mechanical properties.

[0079] The present invention also provides a method for preparing an all-solid-state lithium battery, comprising the following steps:

[0080] A1: The layered cathode material and the solid electrolyte are mixed in a mass ratio of 7:3, and then ground into powder to obtain a cathode powder.

[0081] The layered positive electrode material can be LiCoO2, NMC811, etc. In this step, grinding for about 10 minutes is sufficient.

[0082] A2: Weigh an appropriate amount of sulfide solid electrolyte and put it into the mold battery liner, apply a pressure of 100 MPa to press it into a sheet to obtain the first electrolyte layer, then take an appropriate amount of high Young's modulus solid electrolyte and evenly place it on one side in the thickness direction of the first electrolyte layer, and apply a pressure of 150 MPa to press it into a sheet to obtain the second electrolyte layer.

[0083] In this step, the sulfide solid electrolyte can be selected from Li6PS5Cl. Of course, the sulfide solid electrolyte can also be replaced by an oxide solid electrolyte, a halide electrolyte, a nitride electrolyte, a polymer electrolyte, an organic electrolyte or a combination thereof.

[0084] In this step, the high Young's modulus solid electrolyte adopts the high Young's modulus solid electrolyte prepared in Example 1-5.

[0085] A3: Place the positive electrode powder evenly on the side of the second electrolyte layer away from the first electrolyte layer, and apply a pressure of 350 MPa to press the powder into a tablet to obtain a positive electrode active material layer.

[0086] A4: Place a metal indium sheet on the side of the first electrolyte layer away from the second electrolyte layer, apply a pressure of 50 MPa to press the sheet to obtain a negative electrode active material layer.

[0087] A5: Place the inner liner into the mold battery, lock and seal it to make an all-solid-state lithium battery.

[0088] According to the above method, the high Young's modulus solid electrolytes in Examples 1-5 were used to make all-solid-state lithium batteries, which were marked as 1#, 2#, 3#, 4# and 5# respectively.

[0089] The high Young's modulus solid electrolyte in the above step A2 is replaced with the solid electrolytes in Comparative Examples 1 and 2 to prepare all-solid-state lithium batteries, which are marked as 6# and 7# respectively.

[0090] The performance tests were conducted on 1#-7# all-solid-state lithium batteries respectively. The test items are as follows:

[0091] (1) Ionic conductivity test.

[0092] The ionic conductivity was measured by the AC impedance method using an electrochemical workstation. The measurement temperature was room temperature, the frequency range was 1 Hz to 7 MHz, and the constant voltage was 10 mV. The SE powder was cold pressed into pellets at a pressure of 300 MPa using a die with a diameter of 10 mm. The results are shown in Table 2.

[0093] Table 2

[0094] serial number <![CDATA[Ionic conductivity (mS cm -1 ).]]> 1# 1.65 2# 1.69 3# 0.4 4# 1.42 5# 1.45 6# 1.65 7# 1.42

[0095] It can be seen from Table 2 that the lithium ion conductivity of the solid electrolyte provided by the present invention is relatively high, and when the heat treatment method of the material is changed without changing its chemical composition, its ion transport performance is basically not affected, so it is feasible to control its mechanical properties by changing the heat treatment method.

[0096] (2) Cyclic stability test.

[0097] The charge and discharge test was conducted at a current density of 1000 microamperes at a rate of 1C, and the cut-off voltage was 2.6-4.6 volts. The results are shown in Table 3.

[0098] Table 3

[0099] serial number Capacity retention rate 1# 78.37% 2# 80.20% 3# 30% 4# 60% 5# 65% 6# 23.7% 7# 20.13%

[0100] It can be seen from Table 3 that electrolytes with high Young's modulus and high ionic conductivity have better cycling ability, which proves that samples with high Young's modulus have mechanical stability in assembled batteries and are able to resist external deformation, thereby maintaining good particle contact with the positive electrode material and ultimately having better electrochemical performance.

[0101] (3) After 100 cycles of batteries 1# and 6#, their cathode composite materials were subjected to CT testing.

[0102] CT images Figure 1 (Example 1) and Figure 2 As shown in (Comparative Example 1). As can be seen from the figure, the holes in the cathode composite cube of Example 1 are large and connected, indicating that the solid electrolyte has the rigidity to resist crack propagation and the toughness to withstand the cyclic stress applied by the electrode; the holes in the cathode composite cube in Comparative Example 1 are small and isolated, indicating that due to poor stress application, the solid electrolyte particles are broken and powdered, resulting in the majority of the electrolyte samples shown in the slice.

[0103] (4) Focused ion beam scanning electron microscopy (FIB-SEM) testing of 1# and 6# batteries after 100 cycles.

[0104] When the volume of the positive electrode particles expands, Figure 3 (Example 1) The electrolyte can effectively slow down the volume change caused by the LCO particles, thereby maintaining good physical contact between the electrolyte and the positive electrode particles. Figure 4 Larger pores appeared between (Comparative Example 1), and the electrolyte of Comparative Example 1 was pulverized, which resulted in contact failure between the positive electrode particles and Comparative Example 1.

[0105] In summary, by controlling the cooling rate of the electrolyte, the mechanical properties of the electrolyte can be changed. Under the same ion conductivity and transport performance, a high Young's modulus solid electrolyte takes into account both chemical and electrochemical stability and is difficult to deform. At the same time, materials with higher toughness can absorb more energy before the material particles break, and can better overcome volume changes and maintain the integrity of the particles when the volume of the positive electrode particles expands, so that the particles can effectively maintain physical contact, thereby giving the battery a long cycle life. A low Young's modulus solid electrolyte is more likely to undergo volume deformation when the positive electrode material particles expand, and low toughness makes it more likely to cause structural fragmentation and collapse, resulting in a short battery cycle life and poor stability.

[0106] The present invention is not limited to the above optional implementation modes. Anyone who derives other implementation modes under the inspiration of the present invention and any technical solutions falling within the scope defined by the claims of the present invention shall fall within the protection scope of the present invention.

Claims

1. A method for preparing a high Young's modulus solid electrolyte, characterized in that: The following steps are involved: S1: Melting the electrolyte raw materials under dry oxygen-free conditions, with a melting temperature of 405-700°C and a melting time of 1-20h; S2: Rapidly cool the molten liquid electrolyte into a solid block, and the cooling rate is controlled at 600-1200℃ / min; S3: grinding the cooled solid block into powder to prepare a high Young's modulus solid electrolyte; The electrolyte raw material is Li 2+x M x N 1-x Cl6, wherein M is one or more of Y, Er, Yb, Ho, In, La, Sc, Tb, Dy; N is one or two of Zr and Hf; 0≤x≤1.

2. The method for preparing a high Young's modulus solid electrolyte according to claim 1, characterized in that: In step S1, the melting temperature is 405°C and the time is 20 hours, or the melting temperature is 500°C and the time is 15 hours, or the melting temperature is 600°C and the time is 10 hours, or the melting temperature is 700°C and the time is 1 hour.

3. The method for preparing a high Young's modulus solid electrolyte according to claim 1, characterized in that: In step S2, the cooling rate is 600°C / min, 800°C / min, 1000°C / min or 1200°C / min.

4. The method for preparing a high Young's modulus solid electrolyte according to claim 1, characterized in that: The electrolyte raw material is Li 2.5 Y 0.5 Zr 0.5 Cl6、Li 2.6 Y 0.6 Hf 0.4 Cl6, Li3YCl6 or Li 2.5 Yb 0.5 Hf 0.5 Cl6.

5. A high Young's modulus solid electrolyte, characterized in that: The solid electrolyte is obtained by the preparation method of any one of claims 1 to 4.

6. An all-solid-state lithium battery, characterized in that: The invention comprises a positive electrode active material layer, a negative electrode active material layer and the high Young's modulus solid electrolyte according to claim 5, wherein the high Young's modulus solid electrolyte is pressed into a block and arranged between the positive electrode active material layer and the negative electrode active material layer.

7. A method for preparing the all-solid-state lithium battery according to claim 6, characterized in that: The following steps are included: A1: The layered cathode material and the high Young's modulus solid electrolyte are mixed in a mass ratio of 7:3, and then ground into powder to obtain a cathode powder; A2: Weigh an appropriate amount of sulfide solid electrolyte and put it into the mold battery liner, apply a pressure of 100 MPa to press it to obtain the first electrolyte layer, then take an appropriate amount of high Young's modulus solid electrolyte and evenly place it on one side of the thickness direction of the first electrolyte layer, and apply a pressure of 150 MPa to press it to obtain the second electrolyte layer; A3: The positive electrode powder is evenly placed on the side of the second electrolyte layer away from the first electrolyte layer, and a pressure of 350 MPa is applied to press the positive electrode powder to obtain a positive electrode active material layer; A4: Place a metal indium sheet on the side of the first electrolyte layer away from the second electrolyte layer, and apply a pressure of 50 MPa to press the sheet to obtain a negative electrode active material layer; A5: Place the inner liner into the mold battery, lock and seal it to make an all-solid-state lithium battery.

Citation Information

Patent Citations

  • Solid-state battery and preparation method thereof, and electric vehicle

    CN111370751A